Pelatihan Pembuatan Asesmen Pembelajaran Berbasis Kuis Interaktif Bagi Guru Matematika di SMA Pertiwi 1 Padang - Mulia Suryani; Melisa Melisa; Rahmi Rahmi (Publikasi Inspirasi Indonesia, 2024)
The independent learning curriculum requires teachers to innovate by utilizing technology. Therefore, teacher skills are needed in using technology, not only in delivering material but also in designing learning assessments. However, the teacher's knowledge at SMA Pertiwi 1 Padang in designing electronic-based learning assessments is still very limited. As a manifestation of Higher Education's Tri Dharma, community service activities are carried out in the form of training, with the title